Preliminary three-dimensional neutronic analysis of IFBA coated TRISO fuel particles in prismatic-core advanced high temperature reactor. (1st December 2021) - Alameri, Saeed A.; Alrwashdeh, Mohammad
Highlights: Preliminary neutronics analysis for 2D and 3D PAHTR cores. Effectiveness of utilizing IFBA layer in TRISO fuel particles. Homogeneous distribution of IFBA with different thicknesses. Using IFBA coating in TRISO fuel is reducing the core burnup swing. Abstract: In this study, preliminary neutronic calculations were performed in order to provide a basic design of a prismatic-core advanced high temperature reactor (PAHTR) that adapts a mixture of lithium fluoride and beryllium fluoride (Li2 BeF4, known as FLiBe) as a coolant. This work investigates the effectiveness of utilizing an integral fuel burnable absorber (IFBA) as an additional coating layer for the outer surface of the fuel kernel of the tri-structural isotropic (TRISO) fuel particle. A parametric study was performed to attain a targeted cycle length of 60 months and a fuel burnup greater than 90 MWd/kgU for fuel unit cell, and 70 MWd/kgU and 45 MWd/kgU for 2D and 3D full reactor core, respectively, with a uranium enrichment of 19.75 w/o to support non-proliferation goals. This paper discusses the idea of applying homogeneous distribution of IFBA as an additional coating layer with different thicknesses through the reactor core and perform preliminary neutronics analysis on the reactivity control mechanism for both two- and three-dimensionals core. The Monte Carlo Serpent code has been utilized to estimate the core reactivity balance using the cycle length by reducing the burnup swing between the beginning of cycle (BOC) and end of cycle (EOC). This can be done by adopting the innovative idea of covering the outer surface of the fuel kernel with a thin coating layer of IFBA. This technique is utilized in the 3D evaluation of the PAHTR reactor. Additionally, the neutron spectrum, peaking factor (axial and radial), and multiplication factor for the 3D PAHTR reactor core at the BOC, middle of the cycle (MOC), and EOC were compared by taking into account the double heterogeneity nature of the TRISO fuel particles embedded in the graphite matrix.